An anatomical evaluation of the serratus anterior plane block. (20th July 2016) - Mayes, J.; Davison, E.; Panahi, P.; Patten, D.; Eljelani, F.; Womack, J.; Varma, M.
Summary: The serratus anterior plane block has been described for analgesia of the hemithorax. This study was conducted to determine the spread of injectate and investigate the anatomical basis of the block. Ultrasound‐guided serratus anterior plane block was performed on six soft‐fix embalmed cadavers. All cadavers received bilateral injections, on one side performed with 20 ml latex and on the other with 20 ml methylene blue. Subsequent dissection explored the extent of spread and nerve involvement. Photographs were taken throughout dissection. The intercostal nerves were involved on three occasions with dye, but not with latex. The lateral cutaneous branches of the intercostal nerve contained dye and latex on all occasions. The serratus plane block appears to be mediated through blockade of the lateral cutaneous branches of the intercostal nerves. Anatomically, serratus plane block does not appear to be equivalent to paravertebral block for rib fracture analgesia.